Phytochemical screening of ethanol and methanol extract of pimpinella anisum and comparison of antibacterial assays of prevalent organisms in Bangladesh - Rashid, Faiza Noor E (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.